A study of solar thermal absorber stack based on CrAlSiNx /CrAlSiNxOy structure by ion beams - Al-Rjoub, A. (2019)
Renewable energies are foreseen as a major energy resource for next generations. Among several energy sources and technologies available, Concentrated Solar Power (CSP) technology has a great potential, but it needs to be optimised, in particular to reduce the costs, with an increase of the operating temperature and long term stability. This goal can be achieved by tailoring the composition and multilayer structure of films. In this work we present and discuss the results obtained from solar absorber coatings based on nitride/oxynitride structures. A four-layer film structure, W/CrAlSiNx(HA)/CrAlSiNxOy(LA)/SiAlOx, was deposited on stainless steel substrates using magnetron sputtering deposition method. Simulations were performed to establish the best spectral properties of the multilayer stacks with optical constants of single layers and film thickness. The elemental analysis was performed using Rutherford Backscattering Spectrometry (RBS) and Time of flight Elastic Recoil Detection Analysis (TOF-ERDA). To assess the thermal stability of the coatings the samples were thermal annealed at 400°C, in air, and at 600°C, in vacuum. The results obtained by RBS and TOF-ERDA reveal good oxidation resistance and thermal stability. Also, the optical measurements confirm the potential of these materials for the use in CSP technology.